Awadhi Proverbs: Mapping Culture Through Conceptual Metaphor Theory - Zuhair Ahmad (Nexus Publishing, 2025)
This study explores the proverbs of the Awadhi dialect as rich socio-cognitive and cultural texts that encapsulate the lived realities, moral frameworks, and conceptual worldviews of rural communities in Eastern Uttar Pradesh. Far beyond ornamental expressions, Awadhi proverbs function as linguistic vessels for transmitting collective memory, regulating social conduct, and navigating everyday experiences tied to caste, gender, kinship, agriculture, and ritual life. Anchored in conceptual metaphor theory (Lakoff & Johnson, 1980) this qualitative-descriptive research employs native speaker insights and empirical observation to uncover how these proverbs act as cognitive schemas and cultural scripts. By analyzing the ways in which language encodes social hierarchies, behavioral norms, and embodied metaphors, the study reveals how proverbs not only reflect but also shape the socio-cognitive patterns of Awadhi speakers. The metaphorical framing of social roles portraying lower castes as inherently inferior and women as naturally subordinate reveals how everyday language encodes and normalizes social hierarchies, disguising systemic inequality in the familiar guise of folk wisdom. The research positions Eastern Awadhi proverbs as dynamic tools of thought and tradition central to the maintenance of cultural identity and the vernacular imagination.